Respiratory Syncytial Virus Infection Control Challenges with a Novel Polymerase Chain Reaction Assay in a Tertiary Medical Center. (23rd October 2017) - Sendi, Parham; Egli, Adrian; Dangel, Marc; Frei, Reno; Tschudin-Sutter, Sarah; Widmer, Andreas F.
Abstract : OBJECTIVES: To evaluate host characteristics, mode of infection acquisition, and infection control procedures in patients with a positive respiratory syncytial virus (RSV) test result after the introduction of the GenXpert Influenza/RSV polymerase chain reaction (PCR) assay. DESIGN: Retrospective cohort study. PATIENTS: Adults with a positive PCR test result for RSV who were hospitalized in a tertiary academic medical center between January 2015 and December 2016 were included in this study. Our infection control policy applies contact isolation precautions only for immunocompromised patients. METHODS: Patients were identified through 2 databases, 1 consisting of patients isolated because of RSV infection and 1 with automatically collected laboratory results. Baseline and clinical characteristics were collected through a retrospective medical chart review. The rate of and clinical factors associated with healthcare-associated RSV infections were evaluated. RESULTS: In total, 108 episodes in 106 patients hospitalized with a positive Xpert RSV test result were recorded during the study period. Among them, 11 episodes were healthcare-associated infections (HAIs) and 97 were community-acquired infections (CAIs). The mean length of hospital stay (LOS, 40.2 vs 11.2 days), the mean number of room switches (3.5 vs 1.7) and ward switches (1.5 vs 0.4), and the mean numbers of contact patients (9.9 vs 3.8) were significantly longer and higher in the HAI group than in the CAI group ( P <.0001). Surveillance of microbiology records and clinical data did not reveal evidence for a cluster or an epidemic during the 2-year observation period. CONCLUSIONS: The introduction of a rapid molecular diagnostic test systematically applied to patients with influenza-like illness may challenge current infection control policies. In our study, patients with HAIs had a prolonged hospital stay and a high number of contact patients, and they switched rooms and wards frequently. Infect Control Hosp Epidemiol 2017;38:1291–1297